2015
DOI: 10.1080/13576275.2015.1083693
|View full text |Cite
|
Sign up to set email alerts
|

‘We do it to keep him alive’: bereaved individuals’ experiences of online suicide memorials and continuing bonds

Abstract: This paper presents draws on interviews with individuals who have experience of creating, maintaining and utilising Facebook sites in memory of a loved one who has died by suicide. We argue that Facebook enables the deceased to be an on-going active presence in the lives of the bereaved. We highlight the potential of the Internet (and Facebook in particular) as a new and emerging avenue for the continuation of online identities and continuing bonds. Our study offers unique insight into survivors’ experiences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 36 publications
2
33
0
1
Order By: Relevance
“…Sharing stories and pictures with others and engaging in specific activities on their own were also described as important forms of remembrance. These activities are consistent with descriptions found in previous research on grief activities done in response to the loss of a family member (Bell et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Sharing stories and pictures with others and engaging in specific activities on their own were also described as important forms of remembrance. These activities are consistent with descriptions found in previous research on grief activities done in response to the loss of a family member (Bell et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Interviews with 11 individuals who lost a loved one to suicide found that maintaining an existing Facebook profile or setting up a memorial Facebook group provided comfort and distraction from grief. However, this attachment to the deceased's virtual presence became problematic if post frequency on the profile or memorial group declined (Bell et al, 2015). Participants also noted that maintaining the online account could be particularly painful if they wanted to grieve more privately (Bell et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, this attachment to the deceased's virtual presence became problematic if post frequency on the profile or memorial group declined (Bell et al, 2015). Participants also noted that maintaining the online account could be particularly painful if they wanted to grieve more privately (Bell et al, 2015). Qualitative interviews with Facebook users who have navigated postmortem issues on the platform found that while some appreciated the ability to view the deceased's profile and engage with other loved ones virtually, for some it was distressing to see messages that were viewed as inauthentic, receive notifications from Facebook after the deceased's passing, or see a family member actively control the deceased's profile (Brubaker et al, 2013;Pennington, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers are charged not just with providing macro-level analyses like this one, but also with providing qualitative knowledge of how individuals in different cultures and social settings make sense of death and the digital. When it comes to qualitative research, there is already a rich literature upon which to draw (Bell et al, 2015;Brubaker et al, 2016;Kasket, 2012). However, researchers have hitherto mainly focused on North American and European settings -with some exceptions (Choudhary, 2018).…”
Section: Discussionmentioning
confidence: 99%